Legal Protection for Agents as Business Partners in Insurance Product Marketing Cooperation Agreements Carried Out with Life Insurance Companies (Study of District Court Decision No. 939/Pdt.G/2023/PN-Mdn) - Novica Anggrayani Pangaribuan; Joiverdia Arifiyanto; Mulhadi (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study discusses the regulation of the position of insurance agents as business partners in cooperation agreements with life insurance companies, especially regarding the aspect of legal protection in the event of unilateral termination of the relationship. Although agents are often referred to as "business partners", legally they have the status of representatives of insurance companies based on Law Number 40 of 2014 concerning Insurance and POJK Number 69/POJK.05/2016. This legal relationship is regulated in an agency agreement that contains the rights, obligations, and limits of the agent's authority in marketing insurance products. In practice, unilateral termination of the relationship that is not based on legitimate reasons or does not comply with the agreement has the potential to cause disputes. Agents or business partners who are harmed can claim compensation based on breach of contract (Article 1243 of the Civil Code) or unlawful acts (Article 1365 of the Civil Code). In addition, violations of the principle of fair competition can be reported to the KPPU. Therefore, the cooperation agreement must be drafted clearly and fairly, regulating the time period, termination mechanism, and legal protection. The ultimate goal of this regulation is to create legal certainty, balance of rights and obligations, and protection for all parties involved in life insurance agency relationships.